ASSESSMENT OF HUNTERS’ HARVESTED ANIMALS IN TWO BUSH MEAT MARKETS (FUDMA JOURNAL OF SCIENCES, 2023)
In many localities, bush meat trades remains unmanageable and state of the wild where animals are being hunted can be inferred from frequency of returned animals by hunters to bush meat markets. Information on the state of the wild where animals are been hunted were investigated by collecting information on the population of harvested biomass the hunters returned to two Bush meat markets.  On the site market survey was employed for collection of information on harvested animals for twelve weeks. Each animal was properly observed, categorized into age group, sex class and identified to species level. Collected data were subjected to descriptive and Chi-square statistics. A total of 137 harvested animals from eight species were encountered in the two markets and Grasscutter were mostly found in the markets (58). Highest number of harvested biomass were encountered at Omi-Adio Bush meat market (63%). Majority of the animals were of females and adults groups. Significant association was found between the Bush meat markets and the harvested animal species hunters returned there.
Keywords: Bush meat; sex; age group; hunters; market